1989
DOI: 10.1055/s-2007-1014579
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Psychoactive Drug Intake in a Metropolitan Population

Abstract: Together with a survey conducted among the population of Vienna on the prevalence of hypertension, the consumption of psychotropic substances was investigated. In cooperation with a polling institute a quota-sample of 1,470 Viennese over 15 were visited in their homes by 50 physicians trained in interview techniques. The quota-sample comprised 1,470 people (0.959(0/00) of the population of 1,531,346 inhabitants) and was representative in terms of age, sex, social status, and area of residence. The overall prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
6
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 3 publications
5
6
0
Order By: Relevance
“…The past-month prevalence rate for BZD consumption in Lebanon was 9.6%, close to that reported for other countries (1,2,6) and even higher than the prevalence rate in other studies (3,4). We are comparing our national results to those of countries or major cities in western Europe, where access to medical services is easier and the social security system is more functional than in Lebanon.…”
Section: Discussionsupporting
confidence: 79%
“…The past-month prevalence rate for BZD consumption in Lebanon was 9.6%, close to that reported for other countries (1,2,6) and even higher than the prevalence rate in other studies (3,4). We are comparing our national results to those of countries or major cities in western Europe, where access to medical services is easier and the social security system is more functional than in Lebanon.…”
Section: Discussionsupporting
confidence: 79%
“…In Isparta Province, one-year frequency of benzodiazepine use at least one time among individuals aged ≥15 was determined as 2.06%. In o t h e r s t u d i e s , o n e -y e a r f r e q u e n c y o f benzodiazepine use at least one time in Germany, Canada, USA, Sweden and Belgium was reported as 4-7%, 10%, 11%, 14.5%, and 17.6% respectively [12][13][14][15][16]19,20 . Benzodiazepines can be readily obtained from pharmacies without a prescription in Latin America and some Asian countries.…”
Section: Discussionmentioning
confidence: 99%
“…In England, the National Treatment Agency for Substance Misuse (2011) pointed out that determining the frequency of prescriptions and prescription tendencies are among the main aims of the struggle against misuse associated with prescription drugs1 1 . One-year frequency of benzodiazepine use at least one time was reported as 4% -17.6%, worldwide 5,[12][13][14][15][16] . To the best of our knowledge, there is no community-based frequency studies regarding benzodiazepine use in Turkey.…”
Section: Introductionmentioning
confidence: 99%
“…Recent epidemiologic studies have lent support to earlier findings, from national household surveys in the United States (Mellinger et al 1978(Mellinger et al , 1984a, that actual use of benzodiazepines is generally appropriate. Community surveys in the United States (Swartz et al 1991) and Western Europe (Fichter et al 1989;Pakesch et al 1989;Vazquez-Barquero et al 1989) have found significant positive correlations between benzodiazepine use and psychiatric disturbance as measured using standard rating instruments. Among patients of general practices, those who had receipted prescriptions for benzodiazepines scored significantly higher on such ratings than matched controls who had not received such prescriptions (Salinsky and Dore 1987;Gen6e-Badia et al 1988) Other studies of general medical patients in the United States (Haskell et al 1986;Ried et al 1990) and Western Europe (Magni et al 1986;Bellantuono et al 1989;Antonijoan et al 1990) also showed that benzodiazepine users were distinguished by significant psychiatric morbidity; some of these (Magni et aI.…”
Section: Recent Findingsmentioning
confidence: 99%